Estimates of crossbreeding parameters for egg laying performance of crossbreed chickens at Debre Zeit, Ethiopia - Tadesse, M.; Dessie, Tadelle; Dana, N. (2005)
Crossbreeding parameters were estimated for egg production performance ofindigenous Ethiopian and White Leghorn chicken and their crosses at Debre ZeitAgricultural Research Centre, Ethiopia. The GLM procedure of SAS (1997) wasused to estimate the contribution of additive genetic and heterotic effects in thecrossbreds. Results obtained on average monthly egg production indicate thatindividual breed additive and heterotic effects were large and significant. Breedadditive effects of 5, 13, 14 and 13 eggs/chicken, and individual heterotic effects of5, 6, 4 and 3 eggs/chicken were obtained for the first three, four to six, seven tonine and ten to twelve months of laying periods, respectively. For total eggproduction breed additive effects of 24, 73, 118 and 118, and individual heteroticeffects of 12, 23, 46 and 45 eggs/chicken were obtained for the first three, six, nineand twelve months of laying periods, respectively. Breed additive effect foraverage daily egg production was estimated to be 0.44 for both first six and twelvemonths of laying periods and individual heterotic effect of 0.19 eggs for the first 6months and 0.12 eggs/chickens for the first 12 months of laying periods. Maternalbreed additive and heterotic effects were not significant in all cases. In general eggproduction performance of the crossbred chickens was largely determined bybreed additive genetic effect and the contribution of the heterotic effects wassmall.